Grape Ripening Is Regulated by Deficit Irrigation/Elevated Temperatures According to Cluster Position in the Canopy - Zarrouk, Olfa; Brunetti, Cecilia; Egipto, Ricardo; Pinheiro, Carla; Genebra, Tânia; Gori, Antonella; Lopes, Carlos M.; Tattini, Massimiliano; Chaves, M. Manuela (Frontiers in Plant Science, 2016)
The impact of water deficit on berry quality has been extensively investigated during the last decades. Nonetheless, there is a scarcity of knowledge on the performance of different varieties exposed to a combination of high temperatures/water stress during the growing season and under vineyard conditions. The objective of this research was to investigate the effects of two irrigation regimes (Sustained deficit irrigation (SDI) and regulated deficit irrigation (RDI)) and of two cluster positions within the canopy (east- and west-exposed sides) on berry ripening in red Aragonez (Tempranillo) grapevines. The study was undertaken for two successive years in a commercial vineyard in South Portugal, monitoring the following parameters: predawn leaf water potential, berry temperature, sugars, polyphenols, ABA and related metabolites. Additionally, expression patterns for different transcripts encoding for enzymes responsible for anthocyanin and ABA biosynthesis were analysed. In both years anthocyanin concentration was lower in RDI at the west side (RDIW- the hottest one) from véraison onwards, suggesting that the most severe water stress conditions exacerbated the negative impact of high temperature on anthocyanin. The down-regulation of VviUFGT expression revealed a repression of the anthocyanin synthesis in berries of RDIW, at early stages of berry ripening. At full-maturation, anthocyanin degradation products were detected, being highest at RDIW. This suggests that the negative impact of water stress and high temperature on anthocyanins results from the repression of biosynthesis at the onset of ripening and from degradation at later stages. Irrigation and berry position had small effect on free-ABA concentration. However, ABA catabolism/conjugation process and ABA biosynthetic pathway were affected by water and heat stresses. This indicates the role of ABA-GE and catabolites in berry ABA homeostasis under abiotic stresses. PCA showed the strongest influence in the berry ripening is the deficit irrigation regime while temperature is an important variable conditioning the deficit irrigation success. This work shows the impact of irrigation regime and high temperature interaction in the control of berry ripening during two successive years. Furthermore, berries grown under SDI displayed a higher content in phenolics than those under RDI, with the additional advantage of attenuating negative temperature effects.